Criteria for choosing the energy of micropulse transscleral cyclophotocoagulation - I. E. Ioshin; A. I. Tolchinskaya; I. V. Maksimov (Российский офтальмологический журнал)
For a long time, the main parameter of micropulse cyclophotocoagulation (mTS-CPC) operation planning has been the calculated total energy. However, this indicator alone is not enough to determine more accurate correlations between exposure parameters and treatment outcomes.Purpose: to determine the criteria for choosing energy parameters to be used in mTS-CPC in refractory glaucoma patients.Material and methods. We propose a more reliable indicator of mTS-CPC clinical results, the energy flow, which is calculated from the speed of the probe movement. We developed and used a new strategy for conducting mTS-CPC: dividing the hemispheres of the ocular surface into 4 quadrants for a better control of the light guide movement while maintaining the selected speed. The standardized protocol for conducting the procedure has been modified so that the calculated energy flow is 121.8 J/cm2.Results. The evaluation of the treatment results of 140 patients according to the Kaplan Meier criteria showed the success of the treatment. IOP fell by 30 %, as compared with the baseline in the advanced stage, and by 20 % in the terminal stage, causing no complications. 12 months after the follow-up start, IOP compensation was noted in 81.3 % of cases.Conclusion. The presented modification of mTS-CPC using the energy flow parameters makes it possible to unify the technology of laser treatment, and the results obtained demonstrate a good and uncomplicated hypotensive effect. The availability of standardized energy indicators allows for a selective treatment tactics, depending on the individual characteristics of glaucomatous patients.